Urmilā : ananya prema aura tyāga kī alakshita gāthā - Prabhāta, Āśā, 1958- (Naī Dillī : Rājakamala Prakāśana, 2022)
Novel based on Ūrmilā, Hindu mythological character.
Novel.
"Rāmakathā kī eka apūrva caritra, Lakshmaṇa-bhāryā, ke ananya prema aura tyāga kī alakshita gāthā"--Cover.
Also available as an e-book.
In Hindi.
Keywords: Ūrmilā -- (Hindu mythological character) -- Fiction; Ūrmilā -- (Hindu mythological character); Hindi fiction; Fiction; Fiction; Novels; Romans